Effectiveness of eye-cervical re-education versus motor imagery therapy on chronic neck pain: A randomized controlled trial - Abdel-Aal, Nabil Mahmoud; ElKeblawy, Maher Ahmed; Mohamed Amine, Randa Ahmed (SPORT TK-EuroAmerican Journal of Sport Sciences, 2024)
The aim of this study was to investigate the effect of adding eye cervical re-education exercises (ECRE) versus motor imagery therapy (MIT) to conventional physical therapy (CPT) on pain, functional disability, and cervical range of motion (ROM) in subjects with chronic neck pain (CNP). The study employed a randomized controlled trial design with 60 patients with CNP. Participants were selected from the outpatient clinics of the Faculty of Physical Therapy at Cairo University and were randomly assigned to three groups: conventional physical therapy only (CPT) (Group I, N = 20), eye-cervical re-education exercises plus CPT (Group II, N = 20), and motor imagery therapy plus CPT (Group III, N = 20). All participants received 3 sessions per week for 4 weeks. Visual Analogue Scale (VAS), Neck Range of Motion (ROM) and Neck Disability Index (NDI) were measured at baseline and after 4 weeks of intervention. In terms of pain intensity, neck disability index, neck flexion and extension, right and left lateral flexion, and right and left rotation ROM outcome measures, the results revealed statistically significant differences between groups (p < 0.05). Group II showed statistically significant improvement compared to both Group I and Group III in all measured outcomes (p < 0.05). Additionally, Group III showed statistically significant improvement compared to Group I in all measured outcomes (p < 0.05). Adding eye-cervical re-education exercises or motor imagery therapy to conventional physical therapy resulted in notable improvements. Eye-cervical re-education exercises, in particular, showed greater benefits in reducing pain, enhancing cervical ROM, and decreasing disability compared to conventional physical therapy alone in patients with chronic neck pain.